Les Propos Mobiles. Catalogue. - Rousseau, Pascal (Paris : Association Projet 10, 1998)
Acconci, Vito ; Allouche, Dove ; Bublex, Alain ; Decroux, Gérald ; Hahn, Clarisse ; Pujol, Noëlle ; Hattan, Eric ; Höller, Carsten ; Laurette, Matthieu ; van Lieshout, Joep ; Matta-Clark, Gordon ; Roche, DSV & Sie ; Simon & Renaud AAA corp. ; Scurti, Franck ; Tobier, Lincoln ; Vaesen, Frédéric ; Zittel, Andrea
Frans
Propos mobiles, 10e arrondissement, Paris, Association Projet 10, Paris, 24 Oct. - 15. Nov. 1998
kunstcatalogus